The role of protozoa in the etiology of chronic urticaria - Aziz Ramazan Dilek; Nursel Dilek; Yunus Saral; Saliha Ekşi (Wolters Kluwer Medknow Publications, 2012)
Background: Urticaria is a condition characterized by short-lived swellings of the skin, mouth, and genitalia due to transient leakage of plasma from small blood vessels into the surrounding connective tissues. Although infectious agents such as bacteria and virus causing acute urticaria have been reported previously, very little research has been carried out to understand the relationship between parasitosis and urticaria. This study was designed to contribute to the understanding of the relationship between parasitosis and urticaria. Methods: A total of 49 patients with chronic urticaria and 36 healthy participants were included in the study. Three stool samples were taken from each patient on different days before treating the patients with antiparasitic drugs. Fecal parasite concentrator and native Lugol's method were used for the microscopic examination of the stool samples. Stain samples were prepared by acid fast and modified trichrome stain methods. Serum immunoglobulin E (IgE) levels of both groups were measured using the nephelometric method. Results: Our results revealed that protozoa were detected in 38.8% of patients and in 11.1% of healthy participants. There was a fourfold increase in the total serum IgE levels of patients detected with protozoa when compared with patients in whom protozoa were not detected. Conclusion: In patients who have urticaria with undetectable etiology, stool parasite screening would be prudent and identification of parasite-specific IgE in patients with urticaria would be useful in defining the mechanisms by which the parasite causes these lesions.